2011
DOI: 10.1039/c0em00602e
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and behavior of pharmaceuticals, steroid hormones, and endocrine-disrupting personal care products in wastewater and the recipient river water of the Pearl River Delta, South China

Abstract: The occurrence and behavior of b-blockers, antiepileptic drug carbamazepine and its metabolites, X-ray contrast agent iopromide, natural and synthetic hormones, and several groups of hormone-like personal care products (PCPs), including antiseptics (triclocarban, triclosan, and 2-phenylphenol), parabens and bisphenol A, were investigated in municipal wastewater, sewage sludge, and urban river water of the Pearl River Delta, South China. The pharmaceuticals, natural hormones and PCPs were ubiquitously detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 144 publications
(70 citation statements)
references
References 64 publications
8
61
0
1
Order By: Relevance
“…3, the mass change percentages of total parabens ( PBs) were 26%, 6%, −6%, and −5% in anaerobic tank, anoxic tank, oxic tank and secondary clarifier, respectively. The high mass change in the anaerobic tank suggested that parabens were mainly biodegraded in this unit, which is in accordance with previous report that levels of the parabens decreased significantly during anaerobic processes, the first treatment unit in a sewage treatment plant [31]. However, several studies have reported that these compounds are readily biodegradable under aerobic conditions, while only partially degraded under anaerobic conditions [37,38].…”
Section: Analytessupporting
confidence: 90%
See 1 more Smart Citation
“…3, the mass change percentages of total parabens ( PBs) were 26%, 6%, −6%, and −5% in anaerobic tank, anoxic tank, oxic tank and secondary clarifier, respectively. The high mass change in the anaerobic tank suggested that parabens were mainly biodegraded in this unit, which is in accordance with previous report that levels of the parabens decreased significantly during anaerobic processes, the first treatment unit in a sewage treatment plant [31]. However, several studies have reported that these compounds are readily biodegradable under aerobic conditions, while only partially degraded under anaerobic conditions [37,38].…”
Section: Analytessupporting
confidence: 90%
“…Limited information is available regarding the presence of parabens in the tertiary effluents. In the present study, the concentrations of parabens were similar to or lower than those reported in the tertiary effluents treated with chlorine in China (MeP: 5.1 ng/L; EtP: 1.0 ng/L; PrP: 7.2 ng/L; BuP: 0.3 ng/L) [31], and with coagulation flocculation and filtration in Spain (MeP: 11 ng/L; EtP < 1.5 ng/L; PrP < 0.5 ng/L; BuP < 0.5 ng/L) [32].…”
Section: Tertiary Effluentsupporting
confidence: 82%
“…1). Detailed description of the STP was provided previously (Yu et al, 2011). Briefly, it has three parallel treatment lines with a total capacity of 550 000 m 3 d −1 , serving a population of about 1.5 million.…”
Section: Wastewater Samplesmentioning
confidence: 99%
“…Sample treatment and chemical analysis were performed by employing protocols described previously Tang et al, 2009;Yu et al, 2011). In short, groundwater and reservoir water samples (500 mL each) were spiked with isotope-labeled internal standards and concentrated by solid phase extraction (SPE) on HLB cartridges (200 mg, Waters, Massachusetts, USA) at pH 4.2, pH 4.0, and pH 7.0 for the anti-bacterials, the acid pharmaceuticals and azole antifungals, and the endocrine disruption personal care products (PCPs), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Trace amounts of clotrimazole and miconazole were detected in the procedural blanks and were appropriately subtracted from the reported concentrations of the samples. Detailed information about the QA/QC procedure was provided elsewhere (Huang et al, 2010;Tang et al, 2009;Yu et al, 2011).…”
Section: Quality Assurance and Quality Controlmentioning
confidence: 99%